Sustainable healthcare architecture - Guenther, Robin; Vittori, Gail.; ebrary, Inc. (Hoboken, N.J. : John Wiley & Sons, Inc., 2013)
"Written by two national leaders in sustainable design, a principal at Perkins + Will and a former chair of the board of USGBC, this is the key guide to designing sustainable health care facilities. Fully updated with the latest sustainable design information, new project case studies, and performance metrics LEED for Healthcare (new in 20II) and the online Green Guide for Health Care, the book covers hospitals, ambulatory care, wellness centers, subacute care, and rehabilitation centers. It also includes a number of new guest contributor essays on sustainable design topics specific to healthcare facilities"--
pt. 1. Context -- pt. 2. Actualizing the vision -- pt. 3. Sustainable healthcare today -- pt. 4. Visioning the future.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Hospital architecture -- Environmental aspects; Health facilities -- Design and construction -- Environmental aspects; Sustainable architecture; Electronic books